Writings of intimacy in Romina Paula, or an extended review - Araudo, Leilén (2023)
Paula, R. (2020). Archivos de Word. Mansalva. Paula, R. (Directora). (2019). De nuevo otra vez [película]. Varsovia Films. Paula, R. (2013). Fauna. Entropía. Paula, R. (2005). ¿Vos me querés a mí? Entropía.